Strategi Komunikasi Humas Dalam Meningkatkan Citra Positif Di Universitas Sari Mutiara Indonesia - Nanda Maretta Marbun; Lidia Grace Giawa; Manisari Loi (Universitas Sari Mutiara Indonesia, 2023)
This research is motivated by the importance of a positive image in supporting the reputation and competitiveness of higher education institutions, particularly at Sari Mutiara Indonesia University. The study aims to determine the image held by Sari Mutiara Indonesia University, analyze the communication strategies used by the Public Relations in enhancing the university's positive image, as well as identify the obstacles and efforts that affect the formation of that image. This research employs a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The validity of the data is tested through source and technique triangulation. The research results show that the Public Relations of Sari Mutiara Indonesia University utilizes various media channels, including social media, official websites, and mass media, to convey positive information related to academic activities, student achievements, and institutional collaborations. Public Relations also builds relationships with various parties through community approaches, discussion forums, and creative campus programs to bring the university closer to the public. Although the response from the public is generally good, challenges still exist, such as the lack of participation from some students and the general public. As a solution, Public Relations continues to engage in collaborative approaches, two-way communication, and collaborates with various stakeholders to strengthen the university's positive image.